Efficacy of Prednisone in Children with Acute Nonspecific Mesenteric Lymphadenitis: A Pilot Study - Pavlovic, Momcilo; Rokvic, Zeljko; Berenji, Karolina (Acta medica (Hradec Kralove), 2022)
BACKGROUND: Acute nonspecific mesenteric lymphadenitis (ANML) is a common cause of acute abdominal pain in children with no specific treatment. METHODS: A total of 13 patients (6 boys, 7 girls) aged 7.3 (5-13.5) years with severe acute abdominal pain were evaluated using ultrasonography and laboratory tests to establish the diagnosis of ANML. They were treated with prednisone 1 mg/kg (max 40 mg daily) for a maximum of 5 days. The intensity of abdominal pain was evaluated before and after treatment using a numeric rating scale. RESULTS: All patients had pain scores above 6/10 before, and below 4/10 after treatment with prednisone. Intensity of abdominal pain after treatment for 1-5 days decreased significantly (p < 0.001), with no recurrence at follow-up within 3 months. All other pre-existing signs and symptoms, such as nausea, vomiting, anorexia, fever, diarrhea, and constipation were found to disappear with no adverse effects of corticosteroid therapy. CONCLUSION: These results suggest that the treatment with prednisone in selective patients with ANML can reduce the duration of abdominal pain.
Keywords: prednison; Female; children; mezenteriální lymfadenitida; mužské pohlaví; Abdomen, Acute; Humans; Pilot Projects; mesenteric lymphadenitis; lidé; Abdominal Pain; pilotní projekty; ženské pohlaví; Child; Prednisone; lymphoma; Mesenteric Lymphadenitis; bolesti břicha; dítě; corticosteroids; Male; abdominal pain; akutní bolest břicha